Embracing social media: the change and disruption to public relations practices in Malaysia - Zeti Azreen Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research is not intended to examine on the advantages of using social media at work but to explore the constraint and challenges imposed by social media to PR practitioners at work. The study argues that beside positive effects, social media could also bring great challenge to PR practices that are often taken for granted. At present, there is a dearth of research conducted to examine the usage of social media among PR practitioners in developing nations, the challenges and possible disruptions they imposed on PR practices. In view of this gap, this study aims to address the following objectives: (i) to examine the social media usage among PR practitioners at work; (ii) to identify PR practitioners’ perception on the effectiveness of social media as a tool to engage with stakeholders and (iii) to explore plausible risks imposed by social media on PR roles and practices. This study was part of PR profile research project conducted in 2018. More than 300 PR practitioners working in various organizations in Malaysia took part in the survey. The findings among others affirmed that despite a moderate use of social media, PR practitioners continue to perceive social media as effective tools to engage with stakeholders. Ironically, social media were also seen as imposing threats to organizations’ reputation. This study is significant as it contributes to existing literature on the implications of social media use in PR roles and practice in Malaysia.